The efficacy of the food-grade antimicrobial xanthorrhizol against Staphylococcus aureus is associated with McsL channel expression - Mordukhova, Elena A.; Kim, Jongwan; Jin, Haiyan; No, Kyoung Tai; Pan, Jae-Gu (Frontiers in Microbiology, 2024)
Background: The emergence and spread of multidrug-resistant Staphylococcus aureus strains demonstrates the urgent need for new antimicrobials. Xanthorrhizol, a plant-derived sesquiterpenoid compound, has a rapid killing effect on methicillin-susceptible strains and methicillin-resistant strains of S.aureus achieving the complete killing of staphylococcal cells within 2 minutes using 64 µg/ml xanthorrhizol. However, the mechanism of its action is not yet fully understood. Methods: The S. aureus cells treated with xanthorrhizol were studied using optical diffraction tomography. Activity of xanthorrhizol against the wild-type and mscL null mutant of S. aureus ATCC 29213 strain was evaluated in the time-kill assay. Molecular docking was conducted to predict the binding of xanthorrhizol to the SaMscL protein. Results: Xanthorrhizol treatment of S. aureus cells revealed a decrease in cell volume, dry weight, and refractive index (RI), indicating efflux of the cell cytoplasm, which is consistent with the spontaneous activation of the mechanosensitive MscL channel. S. aureus ATCC 29213ΔmscL was significantly more resistant to xanthorrhizol than was the wild-type strain. Xanthorrhizol had an enhanced inhibitory effect on the growth and viability of exponentially growing S. aureus ATCC 29213ΔmscL cells overexpressing the SaMscL protein and led to a noticeable decrease in their viability in the stationary growth phase. The amino acid residues F5, V14, M23, A79 and V84 were predicted to be the residues of the binding pocket for xanthorrhizol. We also showed that xanthorrhizol increased the efflux of solutes such as K+ and glutamate from S. aureus ATCC 29213ΔmscL cells overexpressing SaMscL. Xanthorrhizol enhanced the antibacterial activity of the antibiotic dihydrostreptomycin, which targets the MscL protein. Conclusion: Our findings indicate that xanthorrhizol targets the SaMscL protein in S. aureus cells and may have important implications for the development of a safe antimicrobial agent.